Mapping of planned relocation cases: a foundation for evidence-based policy and practice - Bower, E; Weerasinghe, S; Mokhnacheva, D (Refugee Studies Centre, University of Oxford, 2022)
A recent global mapping exercise on planned relocation offers opportunities to build insights essential for guiding policy and practice.